The reference genomes of four cassava breeding elite progenitors: SM2775-4, CG1141-1, CM9912-167, and SM1127-8 - Zhang, Xiaofei; Bohorquez Chaux, Adriana (2023)
SM2775-4 (CIAT) progenitor for high and stable dry matter and erect plant type CG1141-1 (CIAT) progenitor for good cooking quality CM9912-167 (CIAT) progenitor for high and stable dry matter and erect plant type SM1127-8 (CIAT) progenitor for good cooking quality